(3cJGH GdefThQGJ hYjhf GdeSGFd GdegeGJs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s ((3YHO Gddg Hf YHO Gddg GdebQi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf NGdb GdSehGJ hGdCQV CeG HYO abO ESJNQJ Gddg JYGdi ai JQJjH GdaJGhi GdJi dTjNi djSgd Ydi eWGdYJgG s
(3BNQgG (B:s
(3eSFdI gd KHJ Cf Hf MjGf Mjf Oafhg CQSd Gddg SHMGfg hJYGdi SHMGfI aCeWQJ Ydi bHQg hde JUH MhGdi GdbHQ Ce dG CLGH QVi Gddg Yfg gPG eTghQ ai cJH GdQbGFb hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs